Pemahaman Nasionalisme Santri Siswa di SMP Al-Uswah Semarang - Wasini, Rina; Purnomo, Arif; Nisa, Aisyah Nur Sayidatun (Universitas Negeri Semarang, 2019)
An effective learning can not be separated with a qualified learning process. It needs plan, implementation, and evaluation from a teacher to achieve the qualified learning process. One of the teacher’s tasks before conducting a certain learning is choosing an appropriate learning method to encourage the students in order to achieve a good learning output. The appropriate learning method to encourage the students’ learning output is show and tell method. The objectives of this research are: (1) to explain the learning output of social science’s students with the use of show and tell learning method, (2) to explain the learning output of social science’s students with the use of leaturing method, and (3) to analyse the significant differences between the learning output with the use of show and tell learning method and leaturing method. The method of this research is quasi experimental method. Tests and documentations are used to collect the data. T-test in SPSS program series 16.0 for windows is used to analyse the data. From the research, it can be concluded that social science’s learning using show and tell learning method is more effective than using leaturing method. It is shown in the average score of students’ learning output which followed sosial science’s learning using show and tell learning method is 7,25, higher than the average score of students’ learning output which followed leaturing method which is 6,31. Pembelajaran yang efektif tidak terlepas dari proses pembelajaran yang berkualitas. Untuk mencapai pembelajaran yang berkualitas diperlukan perencanaan, pelaksanaan, dan evaluasi dari seorang guru. Salah satu peran guru sebelum melaksanakan pembelajaran adalah memilih model pembelajaran yang tepat untuk mendorong siswa agar hasil belajar baik. Model pembelajaran yang tepat untuk memacu hasil belajar siswa adalah model pembelajaran show and tell. Tujuan peneltian adalah: (1) menjelaskan hasil belajar IPS peserta didik dengan menggunakan model pembelajaran show and tell, (2) menjelaskan hasil belajar IPS peserta didik yang menggunakan ceramah, dan (3) menganalisis perbedaan yang signifikan antara hasil belajar IPS peserta didik yang menggunakan model pembelajaran show and tell dan yang menggunakan ceramah. Metode penelitian adalah eksperimen semu (quasi eksperiment). Pengumpulan data menggunakan tes dan dokumentasi. Analisis data menggunakan uji-T pada program SPSS seri 16.0 for windows. Hasil penelitian diperoleh simpulan bahwa pembelajaran IPS dengan menggunakan model pembelajaran show and tell lebih efektif dibandingkan dengan menggunakan ceramah. Hal ini ditunjukkan dengan nilai rata-rata hasil belajar siswa yang mengikuti pembelajaran IPS menggunakan model pembelajaran show and tell yaitu 7,25 lebih tinggi dari nilai rata-rata hasil belajar siswa yang mengikuti pembelajaran dengan ceramah yaitu 6,31.